2013
DOI: 10.1095/biolreprod.112.106989
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Expression, Localization, and Function of Tissue Inhibitor of Metalloproteinase 3 (TIMP3) During the Periovulatory Period of the Human Menstrual Cycle1

Abstract: Ovulation involves reorganization of the extracellular matrix of the follicle. This study examines the expression, localization, and potential function of the tissue inhibitor of metalloproteinase 3 (TIMP3) during ovulation in women. The dominant follicle of the menstrual cycle was collected at specified times throughout the ovulatory process: pre-, early, late, and postovulatory. For quantitative studies, the follicle was bisected; granulosa and theca cells were separated and collected. For immunohistochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 48 publications
(57 reference statements)
2
17
0
Order By: Relevance
“…In the human and rat ovary, the high dose of TIMP3 has been found to promote apoptosis of ovarian granulosa cells (Li and Curry, 2009;Rosewell et al, 2013). Our results are consistent with involvement of TIMP3 activation in granulosa cell apoptosis in human and rat.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…In the human and rat ovary, the high dose of TIMP3 has been found to promote apoptosis of ovarian granulosa cells (Li and Curry, 2009;Rosewell et al, 2013). Our results are consistent with involvement of TIMP3 activation in granulosa cell apoptosis in human and rat.…”
supporting
confidence: 88%
“…Additionally, the presence of TIMP3 has been reported in ovaries from mouse (Inderdeo et al, 1996), rat (Curry and Wheeler, 2002), pig (Shores and Hunter, 2000) and human (Rosewell et al, 2013). Although we found that the expression level of TIMP3 in goat ovary is lower, its function on ovary is significant.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Follicles were fixed in 4% formaldehyde, embedded in paraffin, sectioned (7 m), and processed for immunostaining as previously described (16). The sections were incubated in a humidified chamber at 4°C overnight with CCL20 primary antibodies (AF360; R&D Systems) as shown in Table 2 at a concentration of 10 g/mL.…”
Section: Immunostainingmentioning
confidence: 99%